Socio-Psychological Foundations for the Development of Effective Managerial Competence of Educational Institution Leaders - Eshkuziyevich, Turakhonov Abdukarim (Jurnal Psikologi, 2025)
This article explores the socio-psychological foundations for the development of effective managerial competence among leaders of educational institutions. In the context of modern educational reforms, the effectiveness of school leadership has become a decisive factor in the quality and sustainability of the educational process. The article emphasizes the importance of psychological components such as emotional intelligence, motivation for leadership, value orientations, and interpersonal communication skills. It also analyzes the social factors that influence managerial competence, including organizational culture, team dynamics, and role expectations within the institution. Based on a review of contemporary psychological theories and empirical studies, the article outlines key mechanisms for enhancing leadership capacity through targeted psychological training, professional development programs, and reflective practices.